Analisa Penerapan (SMK3) Studi Kasus Proyek Pembangunan Bendungan Tiga Dihaji Paket VI - Revisdah Revisdah; Muhammad Arfan; Nurnilam Oemiati (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2026)
The construction of dams is categorized as a high-risk activity in the infrastructure sector due to the involvement of heavy equipment, complex structures, and intensive manpower. This study aims to analyze the implementation of the Occupational Safety and Health Management System (SMK3) in the Tiga Dihaji Dam Construction Project Package VI, South Sumatera, Indonesia. A quantitative research approach was employed by distributing questionnaires based on ISO 45001:2018 indicators, conducting direct field observations, and interviews with project workers. The sample size was determined using the Taro Yamane formula with a 15% precision level, resulting in 36 respondents out of 192 workers. Data were analyzed using validity tests, reliability tests with Cronbach’s Alpha, and Pearson correlation with the assistance of SPSS 27. The results show that the implementation of SMK3 in this project falls into the very good category, supported by high compliance with helmet and safety shoes usage. However, compliance with certain personal protective equipment, such as masks, safety harnesses, and safety glasses, remains low. These findings indicate that while the contractor has effectively implemented SMK3 according to Government Regulation No. 50 of 2012, further improvement is needed in developing a strong safety culture, particularly in personal protective equipment awareness. In conclusion, SMK3 implementation in the Tiga Dihaji Dam Project has been effective, but continuous training and supervision are recommended to enhance occupational safety performance in future construction projects.